Eleven percent intact PGM3 in a severely immunodeficient patient with a novel splice-site mutation, a case report - Karin E. Lundin (BMC Pediatrics, 2018)
Abstract Background A novel immunodeficiency, frequently accompanied by high serum-IgE, and caused by mutations in the PGM3 gene was described in 2014. To date there are no unique phenotype characteristics for PGM3 deficiency. PGM3 encodes a carbohydrate-modifying enzyme, phosphoglucomutase 3. Null-mutations are quite likely lethal, and to date only missense mutations or small deletions have been reported. Such mutations frequently cause a combination of reduced enzyme activity and protein instability, complicating determination of the enzyme level needed for survival. Here we present the first patient with a homozygous splice-modifying mutation in the PGM3 gene. An A > G substitution at position c.871 + 3 (transcript NM_001199917) is causing a deletion of exon 7 in the majority of PGM3 transcripts. In addition, this case further increases the clinical phenotypes of immunodeficiency caused by PGM3 mutations. Case presentation We describe the symptoms of a 3-year-old girl who was severely growth retarded, had vascular malformations, extensive eczema, multiple food-allergies, and was prone to infections. Unlike the majority of reported PGM3 deficient patients she lacked skeletal dysplasia and had normal neurocognitive development. In addition to the high serum-IgE, she displayed altered T cell numbers with reduced naïve CD4+ and CD8+ T-cells, increased number of activated effector memory CD8+ T cells and aberrant T-cell functions. The patient was homozygous for a new hypomorphic, splice-modifying mutation in the PGM3 gene, causing severely reduced mRNA levels. In the patient’s cells, we observed 5% intact mRNA and approximately 11% of the protein levels seen in healthy controls. Treatment with allogeneic hematopoietic stem cell therapy was planned, but unfortunately the clinical condition deteriorated with multi-organ failure, which led to her death at 3 years of age. Conclusions There is still no specific phenotype identified that distinguishes immunodeficiency caused by PGM3 mutations from other forms of immunodeficiency. The patient described here yields new information on the phenotypic variability among these patients. In addition, since all the synthesized protein is wild-type, it is possible for the first time to estimate the enzyme activity in vivo. The results suggest that1/10 of the normal PGM3 level is sufficient for survival but that it is insufficient for accurate carbohydrate processing.